Kaderisasi Partai Politik untuk Diajukan Calon Legislatif dan Kepala Daerah - Muhammad Rizki Ramadhani (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The purpose of this study is the first, to determine the impact of poor cadre formation in political party organizations on the performance of cadres in the leadership process. Second, to find out why many political party cadres are actually loyal to the general chairman, not to the people. This study uses a research method with the type of normative legal research (normative law research). The data sources used in this study are primary data sources and secondary data sources as well as primary, secondary and tertiary legal materials. The data collection method used was literature research and analyzed using qualitative descriptive analysis techniques. Based on the results of research and discussion, it can be explained as follows. First, Cadreization that is equipped with moral, character, ethical education, or maybe given an understanding of theology, it is hoped that the output of cadres resulting from a cadre procession like this is none other than superior cadres who are broad-minded, become true statesmen, put aside group interests. first and prioritize the common good by placing the interests of the nation and state above all else. Second, this cadre based on threats, instructions, hegemony by scaring cadres is perhaps what makes diaspora cadres just complementary, for decisions requiring compromise from a general chairperson, if there are cadres who are at odds with the general chairperson, which is a concern for cadres, for example as an example there are diaspora cadres who have different understandings or are different in formulating policies and decisions who are afraid of being fired or reshuffled so that their positions are mixed, this is a paradox that has definitely happened in constitutional politics.